New distributional records of rare riffle beetles (Coleoptera: Elmidae) from the Balkan Peninsula - Novaković, Boris B.; Teofilova, Teodora M.; Pandakov, Pencho G.; Živić, Ivana M. (Archives of Biological Sciences, 2020)
Paper description: Data for riffle beetle (Coleoptera: Elmidae) species in the Balkan Peninsula and Southern Europe is lacking. Aquatic beetle samples were taken using multi-habitat sampling. New records of 7 rare riffle beetle species in the Balkan Peninsula are provided. This work contributes to better knowledge of poorly explored riffle beetle ecology, with new information on their occurrence in polluted watercourses. Abstract: We present new data on rare riffle beetle findings (Coleoptera: Elmidae) from the Balkan Peninsula. Larvae and adult elmid beetles were collected during 2007-2018. The following Balkan countries were included in the study: Serbia, Bulgaria, Romania and Bosnia and Herzegovina. Riffle beetle fauna of the Balkan Peninsula is poorly explored due to a lack of data, particularly in southern and eastern areas. The main objective of the study was to add to the knowledge of this group of aquatic insects. New records of 7 riffle beetle species are provided, as follows: Stenelmis puberula Reitter, 1887, Stenelmis consobrina consobrina Dufour, 1835, Potamophilus acuminatus (Fabricius, 1792), Elmis syriaca zoufali (Reitter, 1910), Elmis rioloides (Kuwert, 1890), Limnius intermedius Fairmaire, 1881 and Limnius opacus Müller, 1806, with notes on their occurrence, habitats and co-occurrence with other riffle beetle taxa. Because of the scarcity of species findings, their disjunct distribution and specific ecological requirements, some riffle beetle species are becoming more vulnerable to pronounced human impact. Accordingly, adequate habitat protection is necessary for rare riffle beetle species and for their conservation on the Balkan Peninsula, particularly in small streams. https://doi.org/10.2298/ABS190908006N Received: September 8, 2019; Revised: November 22, 2019; Accepted: November 22, 2019; Published online: February 12, 2020 How to cite this article: Novaković BB, Teofilova TM, Pandakov PG, Živić IM. New distributional records of rare riffle beetles (Coleoptera: Elmidae) from the Balkan Peninsula. Arch Biol Sci. 2020;72(1):129-35.